Process engineering equipment handbook / Claire M. Soares. - Soares, Claire (McGraw-Hill, 2001)
This illustrated guide to the major equipment found in chemical process plants is aimed at engineers charged with operating, specifying and performing basic troubleshooting on the equipment in their environment.